Supply Conditions of the Innovative Public Procurement Market in Poland: A Delphi study - Małgorzata REMBIASZ; Arkadiusz BOROWIEC (Communications of International Proceedings, 2025)
The aim of the study is an attempt to identify the main factors influencing the innovativeness of the public procurement on the supply side of the public procurement market. The motive of the research was also the shortcoming in scientic research in the field in national and foreign literature on the subject. No study has yet attempted to determine to what extent the supply side of the market influences the outcomes related to improving economic innovativeness in Poland. To obtain reliable and credible research results on the supply-side conditions of the innovative public procurement market, a Delphi study was conducted, followed by the application of network thinking methodology. The factors contributing to the improvement of innovativeness of public procurement in the aspect of sustainable development are the following: bureaucracy, expertise, interpersonal skills, EU grants, R&D activities, and legislation. Despite existing legislative solutions for creating innovative products and services, the authorities, as legislators, should support contractors' efforts to increase their participation in tenders, both in frequency and scope.
Keywords: public procurement; innovation; economic policy; Delphi study